A systematic review of digital services in government sector - Rahmat, Rafidah; Salim, Siti Aisyah (2021)
Technological advancement in information and communication technology (ICT) has triggered a positive proliferation of operations in many industries including the government sector. As such, more prior literature looking into aspects that facilitate the effectiveness of technology in the government sector. However, despite the importance and growing interest towards this research area, few attempts have been made to systematically review and incorporate findings from previous studies and to assess the current state of research regarding classifications and benefits of electronic services in the government sector. building on this gap, this study seeks to conduct a systematic review to map the research landscape into a coherent taxonomy. This research focuses the search on any articles that are relatedto: (1) electronic services (e-services) (2) citizen, and (3) local government in four major databases, namely, Web of Science, ScienceDirect, Scopus and IEEE Xplore. The final dataset resulting from the classification scheme includes 67 articles divided into three categories. The first category contains articles that are related to government e-services reviews, the second category contains articles that are related to studies that measure the e-services in government and the third category contains articles that are related to the framework for modelling the government e-services. Finally, these articles will define the fundamental characteristics of this emerging field in terms of the following: motivation for utilizing government electronic services, benefits that impact usage, and recommendations for expanding e- service adoption in the existing literature. Findings from this systematic review are expected to give the current standpoint and future direction for other researchers to explore more on this research area.